Electives in Medical Curriculum- An Insight of Medical Students - Kaur, Gurmeet; Kritika; Arora, Priya (Indian Journal of Community Health, 2023)
Background: Electives include courses that are interest based, where the students are free to choose the course content. NMC has introduced electives in medical curriculum and it has been implemented for the first time in various medical colleges. Aims and Objectives: The objective of this study is to assess the perception of MBBS students regarding Electives program. Methodology: This cross-sectional study was conducted among the first batch of MBBS students that completed the electives program after taking their consent and approval from ethical committee. Electives Experience scale (EES) and Electives Rating Scale (ERS) were developed, tested, and used for this study. Median, inter quartile range, Cronbach’s alpha and Mann Whitney tests were used for analysis. Results: Most of the students learnt theory, practical, AETCOM (ethics & communication), clinical skills and research in both blocks of posting but research was more focussed in block 1 and practical knowledge and clinical skills in block 2. For the Likert scales (EES-1, EES-2, ERS-1, ERS-2 & ERS), Cronbach’s alpha was found to be quite robust for all the scales. Median and inter quartile range were calculated for EES and ERS scores. Mann Whitney test showed significant gender difference for EES-2. If the student had got elective of his/her choice in block 1, the mean ranks of EES & ERS were significantly higher but if the student had got the elective of his/her choice in block 2, significantly higher scores were seen in overall ERS, ERS-2 and EES-2 only. Conclusion: Electives is a welcome addition to the medical curriculum. However, proactive approach from the student is a must to utilize this opportunity to the fullest.